Thesium muasyae (Santalaceae), a new species from the limestone fynbos of the Overberg, South Africa - Zhigila, Daniel A.; Muasya, A. Muthama (PhytoKeys, 2022)
Thesium muasyae , a new species of the family Santalaceae, is described and illustrated. This species has unique morphological and ecological characters, differentiating it from other closely related species of the genus, such as T. karooicum . These characters include plants forming compact shrubs to about 30 cm tall with glabrous surfaces; leaves recurved, to about 4 cm long, terete to triangular, apiculate; flowers placed in lax spikes or borne solitary; and style up to about 2.5 mm long. Ecologically, T. muasyae is endemic to the limestone fynbos in the Overberg, Bredasdorp District, South Africa. Molecular phylogenetic evidence places this species in Subgenus Frisea Section Barbata, as closest sister to T. hispidulum + T. karooicum . A preliminary conservation Red List assessment suggests that T. muasyae is Critically Endangered, based on its population size, area of occupancy and extent of occurrence.